Spatiotemporal analysis of drought severity using SPI and SPEI: case study of semi-arid Borana area, southern Ethiopia - Worku, Mitiku Adisu (Frontiers in Environmental Science, 2024)
Drought is a complex natural hazard that can cause damage to socio-economic and biophysical systems in any climatic region. The main objective of this paper was to analyze the spatiotemporal drought in the semi-arid Borana area of southern Ethiopia from 1981 to 2018.The climate data was obtained from the Ethiopian Meteorological Institute. Standardized precipitation index (SPI) and standardized precipitation evapotranspiration index (SPEI) at 3and 12-month timescales were adopted to characterize drought during these periods and wet seasons in time and space. The results revealed that moderate to extreme drought conditions at various stations frequently hit months stretching from March to June and September to